PkM Ginger Cultivation in Betao Village, Sidrap Regency: PkM Budidaya Jahe Desa Betao Kabupaten Sidrap - Amalia Zul Hilmi; Asmeati Asmeati; Andi Febriana Tamrin (Yayasan Ahmar Cendekia Indonesia, 2023)
Betao Village, Pituriawa District, Sidrap Regency is an area that has a diversity of regional special drinks, one of which is instant ginger (sarabba). The PKM team aims to train (a) Making Appropriate Technology (TTG) in the form of sarabba